Pharmaceutical properties of 'sucupira' (Pterodon spp.) (Brazilian Journal of Pharmaceutical Sciences, 2010)
The plant of the genus Pterodon (Fabaceae, Leguminosae), commonly known as 'sucupira' or 'faveira', are disseminated throughout the central region of Brazil and has frequently been used in popular medicine for its anti-rheumatic, analgesic, and anti-inflammatory properties. In recent years, interest in these plants has increased considerably. The biological effects of different phytoextracts and pure metabolites have been investigated in several experimental models in vivo and in vitro. The literature describes flavonoids, triterpene and steroids, while one paper presented studies with proteins isolated from the genus. This review provides an overview of phytochemical and pharmacological research in Pterodon, showing the main chemical compounds studied to date, and focusing on the relationship between these molecules and their biological activity. Furthermore, this study paves the way for more in-depth investigation, isolation and characterization of the molecules of this plant genus.